Pengaruh Integritas, Obyektivitas, Dan Kompetensi Terhadap Kinerja Aparat Pengawasan Intern Pemerintah (APIP) Dengan Budaya Organisasi Sebagai Variabel Moderasi Pada Inspektorat Daerah Kabupaten Asahan - Erni Murniati; Maya Sari; Eka Nurmala Sari (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This study aims to determine, analyze and test, the effect of integrity on APIP performance. To find out, analyze and test the effect of objectivity on APIP's performance. To find out, analyze and test the effect of competence on APIP performance. To find out, analyze and test organizational culture to moderate the influence of integrity on APIP's performance. To find out, analyze and test organizational culture to moderate the effect of objectivity on APIP's performance. To find out, analyze and test organizational culture to moderate the influence of competence on APIP performance. The object of this research is the Office of the Inspectorate of Asahan Regency. The sample in this study were 36 (Thirty Six) Auditors and P2UPD at the Inspectorate Office of Asahan Regency. The research approach uses quantitative associative. This research uses data analysis method using SmartPLS.3 software which is run with computer media. In this study, the research instrument used was a questionnaire/questionnaire. The variable measurement scale used in this study is to use an ordinal scale in the form of an item scale. The results of this study indicate that the Integrity variable affects APIP performance, Objectivity affects APIP performance, Competence affects APIP performance, organizational culture moderates the influence of integrity on APIP performance, organizational culture moderates the effect of objectivity on APIP performance, organizational culture does not moderate the influence of competence on performance. APIP